Crowdsourcing Geographic Knowledge 2012
DOI: 10.1007/978-94-007-4587-2_11
|View full text |Cite
|
Sign up to set email alerts
|

The Geographic Nature of Wikipedia Authorship

Abstract: The ef fi cacy and use of volunteered geographic information (VGI) is an active research area, but the geography of VGI authorship is largely unknown. Wikipedia is an online collaborative encyclopedia where anyone can edit articles, including those about place. Moreover, Wikipedia's editorial transparency facilitates in situ observations of collective authorship. The empirical study described in this chapter collects 32 million contributions to Wikipedia's geographic articles over 7 years. It fi nds exponentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Some work has also been conducted about the variable amounts and types of representation of places in different languages. By looking at anonymous edits to Wikipedia Hardy et al (2012) and Hardy (2013), found that there is generally a decreasing likelihood of edits to geotagged articles with increasing distance between editor and article.…”
Section: Promises Of Changing Connectivitymentioning
confidence: 99%
“…Some work has also been conducted about the variable amounts and types of representation of places in different languages. By looking at anonymous edits to Wikipedia Hardy et al (2012) and Hardy (2013), found that there is generally a decreasing likelihood of edits to geotagged articles with increasing distance between editor and article.…”
Section: Promises Of Changing Connectivitymentioning
confidence: 99%
“…Moreover, the geographic representativeness of geosocial media vary widely both among different cities and within cities [14]. Several studies have reported the geographical unevenness of volunteered geographic information, in that some areas may be represented by large amounts of data, while other areas very few [57][58][59]. Varying demographic profiles across geographic areas may also contribute to the geographical unevenness of user-generated content.…”
Section: Challenges Of Utilizing Geosocial Mediamentioning
confidence: 99%